A Methodology for Determining a Hospital's Expected Costs for Changes in Patient Load and Service Mix - Duchessi, Peter (Management Science, 1987)
This paper describes a methodology that demonstrates how specific types of patient/cost data can be used to construct a model that predicts the expected increase or decrease in costs associated with a change in patient load, expansion of an existing patient service department, closure of an existing patient service department, or installation of a specific patient service department. Data from a group of New York State hospitals are used to illustrate the development of the model's components that produce cost estimates. A computer-based model is used to demonstrate the methodology's application to a specific hospital. Additionally, a number of program runs that simulate the cost impact of patient load and/or service mix changes are presented. Finally, the methodology's potential management and regulatory applications are discussed.